Penerapan Sistem Manajemen Kesehatan Dan Keselamatan Kerja (K3) Di Fasilitas Kesehatan - Syaiful Bachri; Latifah Latifah; Sahabuddin Sahabuddin; Rahmat Pannyiwi; Djunaedi Djunaedi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Healthcare facilities are work environments with a high risk of accidents and occupational diseases, both for healthcare workers, support staff, and patients. Exposure to biological, chemical, physical, ergonomic, and psychosocial hazards demands the structured and sustainable implementation of an Occupational Health and Safety (OHS) Management System. However, in reality, the implementation of OHS in healthcare facilities still faces various obstacles, such as limited knowledge, low procedural compliance, and a lack of a work safety culture. This Community Service activity aims to increase the knowledge, awareness, and preparedness of healthcare workers in implementing the OHS system in healthcare facilities. Implementation methods include OHS counseling, interactive discussions, occupational risk identification, OHS implementation simulations, and evaluation through pre- and post-tests. The results of the activity indicate a significant increase in healthcare workers' knowledge and attitudes regarding the importance of OHS implementation. This program is expected to support the creation of a safe, healthy, and productive work environment in healthcare facilities.